2017
DOI: 10.1108/aaaj-04-2015-2039
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical framework of external accounting communication

Abstract: Purpose The purpose of this paper is to provide a theoretical framework of external accounting communication in the form of a typology based on perspectives, traditions, and theories from the discipline of communication studies. The focus is accounting communication with external audiences via public written documents outside the audited financial statements, i.e., annual reports, press releases, CSR reports, websites, conference calls, etc. Design/methodology/approach The theoretical framework is based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 129 publications
(181 reference statements)
1
99
0
5
Order By: Relevance
“…The profits and returns earned by private-sector companies from PFI projects were a source of intense policy criticism (see Section 2). In their discussion of silence as a form of communication, Merkl-Davies and Brennan (2017) observe that what organisations do not say is an under-researched question. We examine whether PFI private-sector companies exhibit selectivity by refraining from reporting on PFI profits and returns in PFI-related narratives compared to non-PFI profits and returns in the non-PFI-related narratives.…”
Section: Research Questionsmentioning
confidence: 99%
“…The profits and returns earned by private-sector companies from PFI projects were a source of intense policy criticism (see Section 2). In their discussion of silence as a form of communication, Merkl-Davies and Brennan (2017) observe that what organisations do not say is an under-researched question. We examine whether PFI private-sector companies exhibit selectivity by refraining from reporting on PFI profits and returns in PFI-related narratives compared to non-PFI profits and returns in the non-PFI-related narratives.…”
Section: Research Questionsmentioning
confidence: 99%
“…It was found that communication helped XY to better understand their clients, thus tailoring the services for each individual. Merkl-Davies and Brennan (2017) stated that in accounting, users of the financial statements had different skills and expertise, so it was important to be able to communicate with a range of clients.…”
Section: Client Engagementmentioning
confidence: 99%
“…Legitimacy theory rests on the concept that organizations have implicit ‘license to operate’ contracts with society, and fulfilling these contracts legitimates the organizations and their operations (Cormier et al ., ; Cormier and Magnan, ). The rationale behind mandatory schemes of ESG information is to influence managers in their disclosure decisions, which is a phenomenon well known in accounting as the ‘information inductance’ principle (Prakash and Rappaport, ; Merkl‐Davies and Brennan, ). Previous studies have shown that managers tend to adjust the quality and quantity of ESG disclosures as an anticipated reaction to stakeholder groups, and they actively shape the perceived legitimacy of the company (Sinclair‐Desgagné and Gozlan, ; Brammer and Pavelin, ; Chan et al ., ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%